Maritime border diplomacy - Nordquist, Myron H.; Moore, John Norton, 1937-; Ellis, Judy (Center for Oceans Law and Policy (Series) ;, 2012)
Maritime Border Diplomacy examines critical issues in international maritime boundary disputes together with the important global role of Indonesia, whose maritime boundaries are imperative to its sovereign status identity. Stressing the seminal importance of the UN Convention on the Law of the Sea to world order, international experts analyze root causes of boundary disputes including historical claims and competition for natural resources. Issues of preventative diplomacy and activism in maritime affairs are explored, as are legal issues arising in the context of creating zones of cooperatio.